Antibacterial potential of solid lipid nanoparticles containing anethi aetheroleum was investigated (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The antimicrobial properties of Anethi Aetheroleum-containing solid lipid nanoparticles (SLNs) were investigated in this work. The powerful antibiotic Anethi Aetheroleum is derived from the essential oil of Anethum graveolens. As a result of their capacity to encapsulate bioactive chemicals more effectively and with greater stability, solid lipid nanoparticles are being considered as possible drug delivery vehicles. The primary objective of this research was to determine if SLNs containing Anethi Aetheroleum had any antibacterial effect on a set of pathogenic microorganisms. A modified emulsification-evaporation process was used to generate solid lipid nanoparticles loaded with Anethi Aetheroleum. The physicochemical characterization of the SLNs was done to evaluate their shape, zeta potential, and particle size. Common microbiological procedures for determining if SLNs generated have antibacterial activity include agar well diffusion and broth micro dilution. Researchers tested both pure Anethi Aetheroleum and SLNs loaded with the compound to see which one was more effective against germs. Conclusions SLN encapsulation of Anethi Aetheroleum improved stability and enabled controlled release. Furthermore, it was shown that SLNs had significantly more potent antibacterial activity compared to pure Anethi Aetheroleum. Strong antibacterial actions against Gram-positive and Gram-negative bacteria showed that the SLNs had a broad-spectrum effect.